Productivity Analysis of PT Perkebunan Nusantara VIII Kebun Pasirmalang's Black Tea Processing Process Utilizing Objective Matrix (OMAX) Method (Agroindustrial Journal, 2022)
PT Perkebunan Nusantara VIII Pasirmalang (PTPN VIII) is a tea processing industry that has effectively transitioned into a shareholder in black tea powder. The attainment of tea processing outcomes did not rise in response to the increased demand. In actuality, 2020's product output never quite reached the production goal. The pandemic conditions at the time had an impact on black tea processing as well. The company hasn't looked into the causes of unsteady manufacturing in more detail. Consequently, in order to assess the performance of the business, production productivity must be measured. By using a variety of input elements to determine the company's performance value, the Objective Matrix (OMAX) method is the tool utilized. Three inputs are taken into consideration while calculating productivity: labor, electricity, and raw materials. The OMAX method was used to measure manufacturing process productivity, and the results indicate that in 2020, December 2020 had the best achievement and February 2020 saw the lowest.